A material for the teaching of ‘The Conquest of the Wallmapu (1879-1885)’ - Salto, Victor (Universidad Nacional del Litoral, 2020)
Currently, there is a varied production of knowledge that has enriched what is known about the conquest of the Wallmapu between 1879 and 1885. A subject that, at least in the primary and secondary schools of the Alto Valle de Rio Negro and Neuquén (Argentina), forms part of the prescribed and taught curriculum; it has a classic presence in school editorial proposals and in teaching practices at these educational levels in the region. The purpose of this article is to communicate a material that contributes to its teaching, initially distinguishing some aspects of what is known about the subject, then identifying some problems and challenges in its teaching and raising the perspectives and didactic foundations that guided its development. Finally, the material is presented and some aspects of it are highlighted in concrete experiences in teacher training and in its use with primary school students.